Robotic Single-Site Resection of Ureteral Endometriosis with Additional Ports - Duan, K. (J Minim Invasive Gynecol, 2020)
STUDY OBJECTIVE: To demonstrate the feasibility and advantages in applying the robotic system with additional ports to single-site laparoscopic resection of ureteral endometriosis. DESIGN: Video presentation of surgical techniques. SETTING: University hospital. PATIENTS OR PARTICIPANTS: Three patients with endometriosis obstructing the ureter(s). INTERVENTIONS: A bipolar grasper, wristed needle drivers, and scissors with monopolar energy were used. Additional ports were inserted due to the complexity of the operation. Entry was made at the umbilicus and carried down into the abdominal cavity, and the pelvis was inspected for endometriosis lesions. The first patient was a 38-year-old G0P0 with an absent right kidney and ureter from a congenital Mullerian fusion defect who complained of one-year duration of pelvic pain. Superficial endometriosis nodules were identified on the left ureter. The lesions were trimmed with cold scissors to avoid thermal damage. The second patient was a 44-year-old G1P1001 who presented with left kidney failure following a longstanding history of chronic pelvic pain and endometriosis with urinary symptoms. Multiple gynecologic procedures were required, including resection of bilateral deep-infiltrating endometriosis lesions, total laparoscopic hysterectomy with bilateral salpingo-oophorectomy, and lysis of adhesions. Structured segments of the left ureter were excised and then left ureteroneocystostomy was carried out. The third patient was a 33-year-old G0P0 with recurrent Stage IV endometriosis who had bilateral ureteral strictures. Bilateral robotic laparoscopic ureterolysis and ureteroneocystostomy were indicated. Notably, for the anastomosis, the bladder was sufficiently mobilized and a Psoas hitch was performed on the right to ensure no tension at the repair site. MEASUREMENTS AND MAIN RESULTS: Final abdominal survey was performed, and hemostasis was ensured. All patients had successful outcomes with minimal blood loss and no known complications to date. CONCLUSION: Robotic-assisted single-site laparoscopy with additional ports is an effective method for ureteral endometriosis removal. A combined effort between gynecology and urology may be needed for highly advanced cases.